The Drosophila segment polarity gene patched is involved in a position-signalling mechanism in imaginal discs. - Phillips, R.G.; Roberts, I.J.H.; Ingham, P.W.; Whittle, J.R.S. (Development, 1990)
We demonstrate the role of the segment polarity gene patched (ptc) in patterning in the cuticle of the adult fly. Genetic mosaics of a lethal allele of patched show that the contribution of patched varies in a position-specific manner, defining three regions in the wing where ptc clones, respectively, behave as wild-type cells, affect vein formation, or are rarely recovered. Analysis of twin clones demonstrates that the reduced clone frequency results from a proliferation failure or cell loss. In the region where clones upset venation, they autonomously fail to form veins and also non-autonomously induce ectopic veins in adjacent wild-type cells. In heteroallelic combinations with lethal alleles, two viable alleles produce distinct phenotypes: (1) loss of structures and mirror-image duplications in the region where patched clones fail to proliferate; (2) vein abnormalities in the anterior compartment. We propose that these differences reflect independently mutable functions within the gene. We show the pattern of patched transcription in the developing imaginal wing disc in relation to the expression of certain other reporter genes using a novel double-labelling method combining non-radioactive detection of in situ hybridization with beta-galactosidase detection. The patched transcript is present throughout the anterior compartment, with a stripe of maximal intensity along the A/P compartment border extending into the posterior compartment. We propose that the patched product is a component of a cell-to-cell position-signalling mechanism, a proposal consistent with the predicted structure of the patched protein.